The Preliminary Title of the New Peruvian Labor Proccess Law and employment quotas in the Regulation of the New General Law of People with Disabilities. Interview with Pedro Morales Corrales - Monge Morales, Gonzalo J. (2014)
The concern for the rights of people with disabilities is not an issue unrelated to Labor Law. From the ban on firing a worker with a supervening disability to permissions for medical treatments, the fact is that Labor Law has provided various special protections.However, recent regulations provide additional protection for people with disabilities: The New Labor Procedure Act and the Regulation of the General Law on Persons with Disabilities. In this interview, the subject of the duties imposed to the employer is treated, as well as their implications on labor relations.